Gamification to Study Machine Learning using Octalysis Framework - Monika Evelin Johan; Samuel Ady Sanjaya; Andreas Yogi Brata; Andrew Brillyant (ULTIMATICS, 2023)
Machine learning is an area of study that enables computers to learn and improve their performance without explicit programming. Its primary application is assisting humans in processing vast amounts of data. Machine learning is a crucial area of study, and to assist students in learning about it, a gamification application has been developed using the Android platform. The aim of this research is to not only provide knowledge to students but also make the application interesting by using the octalysis framework. The application's level of acceptance will be tested on students at Multimedia Nusantara University who are taking machine learning courses. The Unified Theory of Acceptance and Use of Technology Model (UTAUT) method will be used to evaluate the application, which received an average score of 86.77%. This score indicates that students strongly agreed that the gamification approach using the octalysis framework and Android platform for machine learning was well-received.